The Perverse Effect of Flexible Work Arrangements on Informality - Edoardo Di Porto; Pietro Garibaldi; Giovanni Mastrobuoni; Paolo Naticchioni (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Flexible work arrangements (FWAs) are often promoted as a means to regularise informal labour. Utilising unique Italian administrative data that links employer-employee records, daily voucher usage by firms, and randomly timed labour inspections (2014-2017), we demonstrate that FWAs can also hinder enforcement and increase undeclared work. We document that, upon inspection, some firms validate undeclared work with FWAs on the spot, raising the probability of FWA usage by 0.88 percentage points (18%) on average, with the largest increases occurring on the day of and the day after the inspection. A simple partial-equilibrium labour-demand model with heterogeneous tax morale rationalises these "on-the-spot" validations as an enforcement-avoidance margin. The post-inspection increase vanishes when firms are required to pre-notify the tax authority of their use of FWAs. Moreover, when FWAs are completely abolished, presumptive misusers substitute FWAs with temporary contracts.
Keywords: J23; H26; 330; informality; labour vouchers; flexible work arrangements; occasional work; zero-hour contracts